ANALISIS GESER LENTUR BALOK-T KOMPOSIT BETON RINGAN-NORMAL DENGAN METODE ELEMEN HINGGA - MIRANI, ZULFIRA
The study deals with the shear behavior occuring on the contact surface between the flange and the web of a T-Shape composite concrete beam, in which the flange was made of lightweight concrete and the web of normal weight concrete The shear behavior of the beam was inspected with respect to the variations of the type of shear reinforcement, by using an analytical finite element model to fit the results obtained out of laboratory testing. With shear reinforcing bar diameter and web concrete strength as parameters, analytical results out of the implementation of SAP 2000 package program were adjusted to the result based on laboratory test. Analytical result showed that with shear reinforcements provided diagonally between flange longitudinal reinforcement and the web tensile reinforcements, the performance of the beam to resist slip was increased. Keywords: T-Shape composite concrete beam., flange, web, lightweight concrete, normal weight